2010
DOI: 10.1016/j.otsr.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Humerus pathological fracture revealing biliary carcinoma

Abstract: Tumors of the biliary tract are rare, and their survival prognosis is short since diagnosis is often made at advanced stages of the disease. Diagnosis remains difficult because symptoms are often unspecific. Bone metastasis from biliary carcinoma are rare. We report a case of a humeral metastasis revealing a biliary carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The patient was managed with a combination of bisphosphonates, radiotherapy and chemotherapy. The case of a man aged 58 years with a low-energy proximal humerus fracture was reported by Lahrach et al 6 Pathology from theatre revealed metastatic CCA, confirmed via a CT scan, with the patient dying 3 months later. A woman aged 75 years was presented by Karanjia et al 8.…”
Section: Discussionmentioning
confidence: 88%
“…The patient was managed with a combination of bisphosphonates, radiotherapy and chemotherapy. The case of a man aged 58 years with a low-energy proximal humerus fracture was reported by Lahrach et al 6 Pathology from theatre revealed metastatic CCA, confirmed via a CT scan, with the patient dying 3 months later. A woman aged 75 years was presented by Karanjia et al 8.…”
Section: Discussionmentioning
confidence: 88%
“…Only five cases of metastasis to the appendicular skeleton from CCA have been reported in the literature to date ( Table I). The most commonly reported sites of bone metastasis are the humerus, fibula and femur (8)(9)(10)(11)(12). To the best of our knowledge, this is the first report of a scapular metastasis from CCA to date.…”
Section: Discussionmentioning
confidence: 94%
“…There are very few publications in the literature reporting bone metastasis secondary to ICC [9][10][11][12]15]. In the literature, Carlisle et al, Lahrach et al, and Federico et al reported metastatic humeral fractures related to ICC [9][10][11]. Karanjia et al reported a case with distal fibular metastasis secondary to ICC [12].…”
Section: Discussionmentioning
confidence: 99%
“…ICC metastasis to the appendicular skeleton is extremely rare. There are very few publications in the literature on this subject [9][10][11][12]. Three of these publications were related to metastasis of the cholangiocarcinoma to the humerus and one was related to metastasis to the distal fibula.…”
Section: Introductionmentioning
confidence: 99%